Hubungan Pengetahuan Ibu Tentang Infeksi Saluran Pernapasan Akut Dengan Perilaku Pencegahan Infeksi Pernapasan Akut - Agustina, Fitri; Sulistyarini, Wahyu Dewi (MNJ (Mahakam Nursing Journal), 2024)
Background: Acute Respiratory Infection (ARI) is one of the health problems that often occurs in toddlers, especially in developing countries. ARI can cause high morbidity and mortality in children under the age of five. Good maternal knowledge about ARI will increase good ARI prevention behaviour. Purpose: This study aimed to determine the relationship between maternal knowledge about Acute Respiratory Infection and ARI prevention behaviour in toddlers Method: This study used a descriptive-analytical design with a cross-sectional design involving 120 respondents selected by non-probability sampling with accidental sampling techniques. Data were collected through a questionnaire that had been tested for validity previously. Data analysis was conducted using univariate and bivariate methods and the chi-square test. Results: good knowledge about ARI and good ARI prevention behaviour in their toddlers. Up to 80% of respondents had good knowledge about ARI, and 75% had good knowledge about ARI prevention behaviour. Bivariate analysis showed a significant relationship between maternal knowledge about ARI and toddler ARI prevention behaviour (p <0.000). This finding showed the importance of adequate knowledge in improving ARI prevention behaviour in toddlers. Conclusion: This indicates a significant relationship between knowledge and ARI prevention behaviour in toddlers at UPT Sotek Health Center